2017
DOI: 10.3390/sports5040074
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Actual Fundamental Motor Skill Proficiency, Perceived Motor Skill Confidence and Competence, and Physical Activity in 8–12-Year-Old Irish Female Youth

Abstract: This study examines the relationship between actual fundamental motor skill (FMS) proficiency, perceived motor confidence and competence, and physical activity (PA) among female children (n= 160; mean age = 10.69 ± 1.40 years). The Test of Gross Motor Development-2nd Edition (TGMD-2) was used to assess seven FMSs (locomotor, object-control, and stability). Motor confidence and competence were assessed using a valid skill-specific scale, and a modified version of the Self-Perception Profile for Children. PA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…This may be the optimal entry level age for the female participants to transition (at some stage over a 4-year period) into club-based sport. It would seem that a person starting to play sport at age 10 or older may be limited in their competency compared to those who have played for several years [ 22 ], and perceived competency and motor control for children is a significant predictor of involvement in sport and physical activity more generally [ 11 , 29 ]. Furthermore, this current study demonstrates that if female children start playing organised sport at a very early age, this may hinder transitioning from the modified form to club competition in that particular sport.…”
Section: Discussionmentioning
confidence: 99%
“…This may be the optimal entry level age for the female participants to transition (at some stage over a 4-year period) into club-based sport. It would seem that a person starting to play sport at age 10 or older may be limited in their competency compared to those who have played for several years [ 22 ], and perceived competency and motor control for children is a significant predictor of involvement in sport and physical activity more generally [ 11 , 29 ]. Furthermore, this current study demonstrates that if female children start playing organised sport at a very early age, this may hinder transitioning from the modified form to club competition in that particular sport.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Irish study investigating the relationship between physical motor skills proficiency and perceived physical self-concept levels among adolescents found a significant correlation between both variables for females [11]. Physical self-concept has been shown to be related with physical motor skills (i.e., agility, movement speed .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have suggested that a large proportion of children are unable to perform age-appropriate FMS (11)(12)(13) and therefore speci c and sensitive screening of FMS pro ciency in schools may be valuable in helping to identify children with FMS de cits, opening up the possibility of providing additional targeted support. It is known that early identi cation of motor skill problems is bene cial (14), thus Primary schools would be an ideal location for such assessments.…”
Section: Introductionmentioning
confidence: 99%